2010
DOI: 10.1177/0017896910364886
|View full text |Cite
|
Sign up to set email alerts
|

Emergency contraception education for health and human service professionals: An evaluation of knowledge and attitudes

Abstract: Objective: To assess the knowledge and attitudes of health care providers, health educators, and social service providers before and after a training session on emergency contraceptive pills. Design: A survey study using pre—post training measurements. Setting: Two hundred and twenty-three medical, social service, and health education providers in receiving a 2.5-hour training session at their work site. Methods: Human subjects approval was obtained from an Internal Review Board. Anonymous surveys were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In this review no studies were found that examined the pre and in-service curriculum of health providers as it pertained to ECP. This concurs with other studies that have found few evaluations of training initiatives for health and human services providers [ 76 ]. Knowledge of useful education and training interventions would help to identify gaps and inconstancies, align curricula with national policy and integrate interprofessional learning opportunities where appropriate.…”
Section: Discussionsupporting
confidence: 92%
“…In this review no studies were found that examined the pre and in-service curriculum of health providers as it pertained to ECP. This concurs with other studies that have found few evaluations of training initiatives for health and human services providers [ 76 ]. Knowledge of useful education and training interventions would help to identify gaps and inconstancies, align curricula with national policy and integrate interprofessional learning opportunities where appropriate.…”
Section: Discussionsupporting
confidence: 92%